Contribuição da polinização entomófila para a produção de frutos de aceroleira - Oliveira, José Eduardo Martins de [UNESP]; Nicodemo, Daniel [UNESP]; Oliveira, Favízia Freitas de (My University, 2015)
The production of West Indian cherry may increase considerably when its flowers are visited by bees. This study aimed to determine the dependence degree of the West Indian cherry Olivier cultivar, concerning the entomophilous pollination, as well as discovering its potential pollinators, by studying its floral characteristics and the behavior of visiting insects. The most common insects were: Centris (Centris) varia (43.9 %), Centris (Centris) decolorata (17.4 %), Centris (Centris) flavifrons (15.6 %), Epicharis (Epicharana) flava (7.6 %), Centris (Centris) nitens (5.9 %), Centris (Hemisiella) tarsata (4.9 %), Tetragonisca angustula (2.5 %) and Trigona spinipes (2.3 %). It was observed that bees from the Centris and Epicharis genera collected oil, while the T. angustula bees collected pollen and the T. spinipes bees cut the flowers. Fructification was higher when the flowers were open to pollination (27 % of fruit production), followed by manual cross pollination (11 %) and restricted pollination (1 %). No fruits were obtained through self-pollination. The Olivier cultivar was highly dependent on entomophilous pollination and the Centris and E. flava bees can perform this service efficiently.
Contribution of entomophilous pollination to fruit production of West Indian cherry plants
Keywords: Fructification; Malpighia emarginata DC; Malpighiaceae; Pollination